PENGEMBANGAN KECERDASAN SOSIAL-EMOSIONAL MELALUI KEGIATAN BERMAIN PADA SISWA KELAS 2 SEKOLAH DASAR NEGERI CICURUG 3 MAJALENGKA - Nurlistianawati, Agistia Indah; Wahyuni, Wita Sri; Kusmana, Suherli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social-emotional intelligence (SEI) refers to individuals’ ability to recognize, understand, and manage their own emotions and those of others, build healthy social relationships, and make responsible decisions. This study aims to describe the development of SEI through play activities among 2nd-grade students at SD Negeri Cicurug 3 Majalengka using a descriptive qualitative approach. Data were collected through semi-structured interviews, direct observation, and documentation. Observation involved all second-grade students during play activities, while in-depth interviews were conducted with four students selected through purposive sampling and one classroom teacher as the key informant. Data were analyzed using qualitative descriptive analysis techniques. The findings indicate that (1) students demonstrated positive development in social intelligence aspects; (2) emotional intelligence showed a generally positive developmental tendency; (3) the teacher acted as an empathic facilitator in supporting SEI development; and (4) the school culture consistently supported the development of SEI. These findings suggest that play activities can serve as an effective and natural medium for fostering social-emotional intelligence in lower elementary school students.